X-ray fluorescence spectrometry analysis of trace elements in fly ash samples of Kemerkoy thermal power plants - Dogan, O; Symsek, Ö; Nuhoglu, Y; Kopya, M; Ertugrul, M (Marcel Dekker Inc, 2001)
Fly ash samples collected by means of an electrostatic precipitator from the lignite-fired Kemerkoy Power Plants of the located in Turkey was analysed using X-ray fluorescence (XRF) technique. Five trace elements, namely Nd, Pa, Sr, Mo and As were quantified using XRF These concentration values can be helpful in developing a environmental pollution abatement approach for various applications of fly ash such as cement manufacture, wastewater treatment, lightweight contraction aggregate, ceramic production, and secondary source in recovery of valuable elements.
Keywords: EDXRF; trace elements analysis; X-ray fluorescence; fly ash samples